Conceived spiritualities fostered by the multiple references regarding the communication of the ‘message’ about Jesus as the Son of God in 1 John - Merwe, Dirk G. van der (HTS Teologiese Studies / Theological Studies, 2018)
The schism referred to in 1 John 2:18 had already taken place within the Johannine community, with specific reference to the divisions between members, about the identity of Jesus Christ. The author nonetheless uses different semantically related verbs for communicating the ‘message’ (1:5; 3:11) about Jesus’ identity, each one with a particular nuance: through ‘speech, declaring’ [ἀπαγγέλλειν, 1:2, 3]; ‘proclaiming’ [ἀναγγέλλειν, 1:5]; ‘confessing’ [ὁμολογεῖν, 1:9; 2:23, 4:2, 3, 15]; ‘testifying’ [μαρτυρεῖν, 1:2; 4:14; 5:6–11] and through ‘writing’ [γράφειν, 1:4; 2:1, 7, 8, 12, 13 (2x), 14 (3x), 21, 26; 5:13]. In the last chapter of 1 John (1 Jn 5:5–12), the author’s testimony (in writing) that there is eternal life in Jesus Christ who is the Son of God culminates when he incorporates the fundamental testimonies of the Father, the Spirit and the water and blood to endorse this. The intention of this research is to determine conceivable spiritual experiences fostered among those early Christians when this message about Jesus as the Son of God, the Christ, was communicated to them through these activities (declaring, proclaiming, confessing, testifying) and confirmed via the testimonies of the Father, the Spirit and the water and blood.
free
Keywords: Bible. Epistle of John I – Language; style; Bible. Epistle of John I – Theology; Confession; Experience (Religion) – Christianity; Open access; Peer reviewed; Rhetoric in the Bible; Witnessing